Application of Aquatic Plants Bokashi on The Growth and Yields of Red Onion (Allium ascalonicum L.) - Panji Surawijaya; Melhanah Melhanah; Mochammad Anwar; Hastin Ernawati Nur Chusnul Chotimah; Raudah Raudah (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
The objectives of the study are to determine the effect of both type and dosage of aquatic plants bokashi on the growth and yield of red onion in alluvial soil. The research design used was Factorial Completely Randomized Design (CRD) consisting of two factors, namely type and the dose of aquatic plants bokashi. The first factor consisted of three types of bokashi, i.e., giant Salvinia (Salvinia molesta), water cabbage (Pistia stratiotes) and water hyacinth (Eichornia crassipes), respectively. The second factor were four levels of bokashi dosage which were 0 tons ha-1, 10 tons ha-1 (0.2 kg/polybag), 20 tons ha-1 (0.5 kg/polybag) and 30 tons ha-1 (0.8 kg/polybag). The study was conducted from March to May 2017, located in the greenhouse of the Department of Agronomy, Faculty of Agriculture, University of Palangka Raya. The results showed that there was no interaction between the type and dose of bokashi on all variables observed. The dosage of bokashi affected plant height, leaf number, fresh weight and dry weight of biomass per clump, dry weight of bulbs and tuber diameter, but did not significantly affect the number of bulbs. The bokashi type did not significantly affect all observed variables. However, the water hyacinth bokashi tended to be better than other treatments